Evidence-based public health: Barriers and facilitators to the transfer of knowledge into practice - Kapil Kumar Singh (Wolters Kluwer Medknow Publications, 2015)
This paper underscores some of the barriers and facilitators in the practice of evidence-based public health (EBPH). A large body of evidence-based interventions (EBIs) exists, which has been generated through highly robust systematic reviews. These EBIs have been widely disseminated and promoted by public health researchers and the World Health Organization (WHO) as effective public health interventions against various preventable/treatable diseases. The inability of many low- and middle-income countries to contextually adapt and effectively implement evidence-informed interventions (EBIs) has been identified as a major obstacle to progress in achieving Millennium Development Goals (MDGs). Hence, it is imperative to identify and understand the factors that are detrimental to the successful transfer of evidence into policy as well as practice. This paper discusses how factors such as political, contextual, and organizational factors; nature of evidence; and community participation influence the practice of EBPH.